Overview of Environmental Laws in Africa: Towards the Emergence of an ‘Africanization’ of Environmental Protection Standards? - Sanae Bouyayachen (Groningen Journal of International Law)
Strengthening the implementation of environmental rules is now a main issue for national and environmental law. The environment theme is far from new and has been closely linked to African experts since the 1960s. Indeed, it was in Africa where one of the first major conventions on the conservation of nature and natural resources was initiated. In many African countries, the field of environmental law is notable for the profusion and variety of principles and regulations concerning the preservation of the environment. However, this abundance of legal standards is at odds with the actual practice of environmental protection due to the vast majority of these environmental rules not being implemented. It is necessary to draw attention to the need for improved articulation of African rights with international environmental law to assist Africa in addressing this challenge. This article analyses how the execution and implementation of current environmental legislation in Africa, with an African specificity, could lead to an ‘Africanization’ of environmental protection, which can also help in resolving the discrepancies that arose when norms of external origin were incorporated into African legal frameworks.